2018
DOI: 10.1186/s12884-018-1966-z
|View full text |Cite
|
Sign up to set email alerts
|

Engaging pregnant women in observational research: a qualitative exploratory study

Abstract: BackgroundRecruitment of pregnant women to population health research can be challenging, especially if the research topic is sensitive. While many pregnant women may be inherently interested in research about pregnancy, there is the possibility that the nature and timing of the project may give rise to anxiety in some women, especially if the topic is sensitive or it brings about new awareness of potential pregnancy complications. Research staff undertaking recruitment need to be skilled at strategies to mana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 18 publications
(21 reference statements)
2
18
0
1
Order By: Relevance
“…The fact that traditional recruitment methods yielded the highest number of participants is not surprising because previous research has found that personable, enthusiastic, non-judgmental, and empathetic recruitment personnel and research staff aid in recruitment efforts [6,54]. Others have shown that recruitment was also improved by working with obstetricians for participant referrals [3,12,49,50], as in the current study.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The fact that traditional recruitment methods yielded the highest number of participants is not surprising because previous research has found that personable, enthusiastic, non-judgmental, and empathetic recruitment personnel and research staff aid in recruitment efforts [6,54]. Others have shown that recruitment was also improved by working with obstetricians for participant referrals [3,12,49,50], as in the current study.…”
Section: Discussionsupporting
confidence: 59%
“…Pregnant women report that they do not participate in research studies because they often lack interest in or distrust scienti c research [6,9,10], experience disapproval from friends and family [3,5], and feel as though they do not have time to participate [5,9]. On the other hand, pregnant women indicate they are motivated to participate when they receive personal bene ts, including the potential for improved pregnancy outcome [48,49], health education [50], and improvements to their own health [10,48].…”
Section: Discussionmentioning
confidence: 99%
“…Employ email or IP and time stamp validation to reduce duplicate and invalid participants. 5. Offer an initial incentive at enrollment that is fair but not overly generous to encourage legitimate enrollment.…”
Section: Lessons Learnedmentioning
confidence: 99%
“…4. Making the surveys easy to complete by optimizing them based on device (ie, desktop vs mobile devices). 5. Providing participants with interaction options (ie, text and email), but being careful not to unnecessarily overburden.…”
Section: Lessons Learnedmentioning
confidence: 99%
“…In addition, enrolling a representative pregnant population may be difficult, as research has shown that African American pregnant women are less willing to take surveys associated with medical research; this can challenge researchers to construct and maintain representative samples [ 3 ]. It has been shown that building trust is pivotal when conducting research among pregnant women and necessary to increase participation [ 5 ].…”
Section: Introductionmentioning
confidence: 99%